Critical View on The Existence of Gambus Tunggal Lampung: Promoting Collaborative Working Between Artists and Stakeholders - Tejapermana, Prisma; Hidayatullah, Riyan (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
The Lampung societies have many arts and cultures, one of which is a gambus tunggal. The characteristic of gambus that are played solely and has an original tuning system. A gambus tunggal style produces a melodic tone,Ã‚Â accompanied by chanted poems that involve new romantic romance of Lampung, or parentsÃ¢â‚¬â„¢ advice to their children. This ethnography study aims to comprehend how the gambus tunggal artists maintain the existence in Lampung. The study applies a descriptive method with a qualitative idea. We have interrogated and field studies to gather primary data. A purposive sampling technique was used to interview a gambus tunggal player who existed for decades. The result indicates that a gambus tunggal artist is doing a collaborative struggle to support gambus tunggal and living sourcesÃ¢â‚¬â„¢ survival. They need collaboration to keep the existence of traditional Lampung music. Gambus players have considered using social media as a promotional strategy. The local governmentÃ¢â‚¬â„¢s role has a tremendous impact, for example, providing an opportunity to perform gambus tunggal at various events, festivals, and many competitions. Therefore, the tourism sector is the foundation of LampungÃ¢â‚¬â„¢s traditional music. It establishes policies to serve various performing arts.